Post-colonial transition, aid and the cold war in South-East Asia : Britain, the United States and Burma, 1948-1962 - Foley, Matthew (2007)
This thesis charts British and American policy-making towards Burma between the country's independence from the United Kingdom in 1948 and the military coup that ended civilian government in 1962. In particular, it examines the role aid played in Burma's relations with the West and China and the Soviet Union: what it was offered, by whom, when and why, and how its leaders responded. Aid from the West began immediately after independence, when the British furnished the Burmese government with military aid against the communist insurgency that broke out in March 1948. Financial assistance was offered, but refused, in 1950. American help began under Harry Truman's administration, also in 1950, and continued under Dwight D. Eisenhower. Further proposals were developed by John F. Kennedy's administration, although these plans were thwarted by the military coup in 1962.